(2m + 7) - (3 - 4m)
First distribute the (-) in front of the quantity of 3 - 4m.
Think of it as this:
-1(3 - 4m)
You multiply each number inside the parenthesis by -1.
So:
3*-1 = -3
-4m * -1 = 4m
Now that you've distributed the negative you can remove the parenthesis.
Now you'll just set it all up like you would any normal problem. Because -3 is negative you'll make it subtract.... I'll show you what I mean:
2m + 7 - 3 + 4m
Combine like terms (Terms which have the same variables... in this case the same number of m's)
Rearranging them can help!
4m + 2m + 7 - 3
6m + 7 - 3
6m + 4, is our difference!
With any parallelogram, the diagonals bisect each other. This is another way of saying that they cut each other in half.
FH is one diagonal that is split into two equal pieces by the other diagonal EG.
The two parts of FH (KH and KF) are congruent to each other, so KH = KF. They combine back to FH
By the segment addition postulate
KH + KF = FH
KH + KH = FH .... KF has been replaced with KH (works because KF = KH)
2*KH = FH
Now use substitution
2*KH = FH
2*15 = FH .... replace KH with 15 (since KH = 15)
2*15 = 4x-2 ... replace FH with 4x-2 (since FH = 4x-2)
and solve for x
2*15 = 4x-2
30 = 4x-2
30+2 = 4x-2+2 ... add 2 to both sides
32 = 4x
4x = 32
4x/4 = 32/4 ... divide both sides by 4
x = 8
----------------------------------------
----------------------------------------
Answer: x = 8
Hello,
(x-(-1+4i))(x-(-1-4i))=((x+1)-4i)((x+1+4i)
=((x+1)²+16
=x²+2x+17